Fremdsprachenlernen in der digitalen, multimodalen Welt. Perspektive der Studierenden - Sierak, Katarzyna (Neofilolog, 2024)
With machine learning-powered digital solutions influencing for eign language learning, it is crucial to understand students’ perceptions of language learning. In this article, multiple questions related to the increasing digitalization of language are discussed. A survey design was employed in this study to understand students’ preferences in institu t ional education versus independent learning. A total of 70 participants completed a questionnaire related to their language learning prefer ences. All the participants enrolled in this experiment were students of Lingwistyka w biznesie [Linguistics in business] at the University of Warmia and Mazury in Olsztyn1. The results focus on how “Digital Na t ives” learn today, what they expect from traditional face-to-face teach ing and how the education system needs to adapt to such demands.